Walkability in Suburbia - Patterson, Lauren (Kansas State University, 2014)
Walkability is a challenge for most suburban metropolitan areas. Specifically, the Kansas City suburban cities of Overland Park, Olathe, Leawood, and South KCMO have sprawled and disconnected urban patterns and a low average walkability score of 37 out of 100 (Walk Score, 2013, https://www.redfin.com/how-walk-score-works/). The Indian Creek Trail, an existing recreational trail that extends throughout the southern Kansas City neighborhoods, has the potential to improve walkability. It connects major destinations, including residential communities, businesses, and commercial districts throughout the suburban neighborhoods. Many studies have analyzed suburban sprawl and walkability, but few studies have identified the possibility of enhancing existing trail systems to provide for greater mobility, connectivity, and activity. The study examines the feasibility of reusing an existing trail system to act as a catalyst to promote walkability in the Kansas City suburbs. The goal of the project to create a paradigm shift in the way people think about transport and development. The purpose is to identify how centering walkable strategies around an active transportation network can promote walkability in sprawled suburban areas. The question: How can focusing improvement around existing trail infrastructure enhance walkability in suburban areas? has guided the project and helped define strategies for improvement. This project identifies the Indian Creek Trail’s current and potential uses from an in depth community and spatial analysis. Surveys, interviews, and observations were conducted within 13 major destination areas along the Indian Creek Trail. The results were then analyzed to create an evidence‐based design framework that will address walkable concerns. The project results showed there were three primary causes for walkable limitations along the trail network: current transportation trends, suburban development patterns, and social perceptions. Understanding these important aspects of walkability helped identify a framework for improvement. The findings from the analysis determined the site restrictions and prospects of creating a walkable environment along the Indian Creek Trail. The results identified primary locations of needed intervention and revealed major opportunities for connection. The design then applied walkable components based on analysis findings to create nodes of complete communities. Design decisions were tailored to amend community needs and alter traditional transport perceptions. The objective of the designs was to address specific walkable limitations to create reasonable solutions in suburban areas. The project identifies 5 primary components of walkability that can be used to create a walkable plan. Future studies would revolve around implementing the designs and analyzing the effectiveness to create a model that can be applied to enhance walkability for other suburban areas. Ultimately, the results could establish how improved walkability can promote multi‐modal transportation opportunities where population, density, diversity, and funding do not allow for typical transportation or development enhancements.
Keywords: Walkability; Trail Networks; Suburbia; Landscape Architecture (0390); Land Use Planning (0536); Transportation (0709)